Feasibility study for assessing liver fibrosis in paediatric and adolescent patients using real-time shear wave elastography - Dhyani, Manish (J Med Imaging Radiat Oncol, 2015)
INTRODUCTION: The objective of this study was to evaluate the feasibility of shear wave elastography (SWE), as a non-invasive means of assessing liver fibrosis stage in paediatric and adolescent patients. MATERIALS AND METHODS: Consecutive paediatric and adolescent subjects scheduled for liver biopsy (LB) evaluation of known or suspected diffuse liver disease were included after informed guardian consent and subject assent in this IRB-approved single institution study. Elastograms were acquired prior to liver biopsy, from the liver under a breath-hold after normal inspiration when possible. Biopsy specimens underwent blinded pathologist review using the METAVIR scoring system. RESULTS: Twenty-four patients (M: F = 13:11) with a mean age of 17 years (range: 1–21 years) underwent liver biopsy. The distribution of fibrosis on pathological examination was: F0 = 10, F1 = 9, F2 = 1, F3 = 3, and F4 = 1. Subjects with stages F0 and F1 fibrosis had a mean SWE value of 6.93 kPa (95% CI: 6.33–7.44 kPa) and 8.33 kPa (95% CI: 6.83–10.80 kPa) respectively. The SWE value for the one subject with stage F2 fibrosis was 6.36 kPa, whereas for F3 and F4 were 8.86 (95% CI: 5.70–11.40) and 17.85 kPa respectively. The correlation between SWE values and fibrosis grade was strong (r = 0.58, P = 0.003), and the area under the ROC curve differentiatiang ≥F2 fibrosis was 0.62 (95% CI: 0.26–0.98). CONCLUSION: Estimation of liver stiffness using real-time SWE is feasible using the SC6–1 ultrasound probe in paediatric and adolescent patients and strongly correlates with the stage of fibrosis.